MENIMBANG METODE JOHN WANSBROUGH DAN FAZLUR RAHMAN DALAM STUDI AL-QURAN - Machrus, Machrus (TEOLOGIA, 2013)
Abstract: One of aspects of Islam studied by orientalists is the Qurâan. They have written many books on the QurâÄn. One of themes of Qurâanic studies written by orientalists are about influences of Judeo-Christianity tradition in the QurâÄn. They try to prove the influences of Judeo-Christianity tradition in the QurâÄn. One of orientalists who try to prove the influences of Judeo-Christianity tradition in the QurâÄn is John Wansbrough, a Jewish orientalist. In studying the QurâÄn, Wansbrough uses literary analysis, an analysis based on the text apart from historical context. He does not believe in historical context relates to Qurâanic revelation. Whereas Qurâanic revelation relates to the events occurred in Muá¸¥ammadâs life time. By using historical approach, Fazlur Rahman proves that qurâanic revelation relates to the history so-called asbÄb al-nuzÅ«l. Rahman insists that the study of the QurâÄn done by Wansbrough does not make sense. Abstrak: Di antara aspek-aspek dalam Islam yang dikaji oleh para orientalis adalah al-Quran. Sudah banyak karya mengenai al-Quran yang dihasilkan oleh para orientalis. Sebagian dari karya orientalis mengenai al-Quran bertemaÂkan pengaruh Yahudi-Kristen dalam al-Quran. Para orientalis mencoba untuk membuktikan adanya pengaruh Yahudi-Kristen. Salah satu dari mereka adalah John Wansbrough. Ia mengkaji al-Quran dengan menggunakan analisis sastera (literary analysis), suatu analisis yang didasarkan pada teks terlepas dari konteks sejarah. Ia tidak mempercayai bukti-bukti sejarah berkaitan dengan turunnya al-Quran. Padahal turunnya al-Quran berkaitan dengan peristiwa-peristiwa yang terjadi masa Nabi Muá¸¥ammad. Hal ini dibuktikan dengan analisis sejarah yang dilakukan oleh Fazlur Rahman. Rahman sendiri dengan tegas mengatakan bahwa kajian terhadap al-Quran yang dilakukan Wansbrough dengan menggunakan analisis sastera tidak masuk akal karena ada banyak kejanggalan. Keywords: analisis sastera, Yahudi-Kristen, pengaruh, sejarah, Bibel.